Simultaneous determination by NIR spectroscopy of the roasting degree and Arabica/Robusta ratio in roasted and ground coffee. (January 2016) - Bertone, E.; Venturello, A.; Giraudo, A.; Pellegrino, G.; Geobaldo, F.
Abstract: The roasting colour of the coffee beans and the varietal composition of the blends are key factors for the development of the sensorial properties of the coffee brew. The former is a critical control parameter for the roasting process and allows to verify quickly the performance of the roasting, being directly related to the desired organoleptic characteristics of the beverage. The varietal composition is a paramount factor for quality, where Arabica species shows a better sensorial profile in comparison to Robusta, with a substantial difference in the selling price. Near infrared spectroscopy associated with chemometrics represents a screening tool when a fast determination of these two coffee parameters is needed. The focus of the work is the elaboration of a unique model for the simultaneous determination of the roasting degree and of Arabica/Robusta ratio. The PLS algorithm was applied and a completely independent external set was used for the validation. A root mean square errors equal to 1.28 A.U. and 4.34% (w/w) was obtained, respectively for the colour and the Arabica content in the blends. Highlights: The roasting colour and the varietal composition are crucial for coffee properties. PLS2 was applied to build a unique model for the colour and the Arabica content. Hotelling's T 2 and Q residuals parameters were used to detect outlier samples. A completely independent external set was used to test the model performance. RMSEP for the colour would it be 1.28 A.U. and for the Arabica content 4.34% (w/w).